The effect of field independence on processing instruction on the acquisition of English passive by Iranian EFL learners. Issue 1 (18th March 2022) - Naami, Amir; Sahragard, Rahman
Abstract : This work reports on a classroom-based study that investigated the role of field independence in the effectiveness of processing instruction. From a high school in Iran, fifty six learners were recruited and randomly assigned to an experimental and a comparison group. The former was taught through processing instruction while the latter received traditional output-based instruction on English passive. A sentence-level interpretation task was used in a pretest-treatment-posttest design to measure instructional effects. The results illustrated that processing instruction significantly improved learners' acquisition of the target structure, whereas the traditional instruction was not effective. Furthermore, no interaction was found between the learners' field independence and their performance in the immediate and delayed posttests. This could be attributed to the unique characteristic of processing instruction and its systematic nature neutralising learners' differences and consequently creating an optimum learning condition benefitting all the learners.